Loss of Mob1a/b in mice results in chondrodysplasia due to YAP1/TAZ-TEAD-dependent repression of SOX9 - Goto, Hiroki; Nishio, Miki; To, Yoko; Oishi, Tatsuya; Miyachi, Yosuke; Maehama, Tomohiko; Nishina, Hiroshi; Akiyama, Haruhiko; Mak, Tak Wah; Makii, Yuma; Saito, Taku; Yasoda, Akihiro; et al. (Development (Cambridge), 2018)
Hippo signaling is modulated in response to cell density, external mechanical forces, and rigidity of the extracellular matrix (ECM). The Mps one binder kinase activator (MOB) adaptor proteins are core components of Hippo signaling and influence Yes-associated protein 1 (YAP1) and transcriptional co-activator with PDZ-binding motif (TAZ), which are potent transcriptional regulators. YAP1/TAZ are key contributors to cartilage and bone development but the molecular mechanisms by which the Hippo pathway controls chondrogenesis are largely unknown. Cartilage is rich in ECM and also subject to strong external forces – two upstream factors regulating Hippo signaling. Chondrogenesis and endochondral ossification are tightly controlled by growth factors, morphogens, hormones, and transcriptional factors that engage in crosstalk with Hippo-YAP1/TAZ signaling. Here, we generated tamoxifen-inducible, chondrocyte-specific Mob1a/b-deficient mice and show that hyperactivation of endogenous YAP1/TAZ impairs chondrocyte proliferation and differentiation/maturation, leading to chondrodysplasia. These defects were linked to suppression of SOX9, a master regulator of chondrogenesis, the expression of which is mediated by TEAD transcription factors. Our data indicate that a MOB1-dependent YAP1/TAZ-TEAD complex functions as a transcriptional repressor of SOX9 and thereby negatively regulates chondrogenesis.